2006
DOI: 10.1523/jneurosci.5095-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Cytoplasmic Dynein ATPase by Lis1

Abstract: Mutations in, but the mechanistic significance of this interaction is not well understood. We now report that recombinant Lis1 binds to native brain dynein and significantly increases the microtubule-stimulated enzymatic activity of dynein in vitro. Lis1 does this without increasing the proportion of dynein that binds to microtubules, indicating that Lis1 influences enzymatic activity rather than microtubule association. Dynein stimulation in vitro is not a generic feature of microtubule-associated proteins, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
82
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(86 citation statements)
references
References 30 publications
2
82
2
Order By: Relevance
“…The LIS1-binding sites on the dynein heavy chain were determined by the yeast two-hybrid assay: one is in the stem region between amino acids 649 and 907, and the other is the AAA1 domain (Taiet al 2002). Whether and how LIS1 affects dynein's ATPase cycle in vivo is still not clear, but an enhancement on dynein's microtubulestimulated ATPase activity by purified LIS1 has been detected in vitro (Mesngon et al 2006). This enhancement on dynein's motor activity is consistent with LIS1's positive role in dynein function.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The LIS1-binding sites on the dynein heavy chain were determined by the yeast two-hybrid assay: one is in the stem region between amino acids 649 and 907, and the other is the AAA1 domain (Taiet al 2002). Whether and how LIS1 affects dynein's ATPase cycle in vivo is still not clear, but an enhancement on dynein's microtubulestimulated ATPase activity by purified LIS1 has been detected in vitro (Mesngon et al 2006). This enhancement on dynein's motor activity is consistent with LIS1's positive role in dynein function.…”
Section: Discussionmentioning
confidence: 66%
“…Further studies have demonstrated that LIS1 and its homologs in higher eukaryotic systems are also involved in cytoplasmic dynein function, and physical interactions between LIS1 and dynein/dynactin have been shown (Liu et al 2000;Sasaki et al 2000;Dawe et al 2001;Tai et al 2002;reviewed by Wynshaw-Boris and Gambello 2001;Gupta et al 2002;Tsai and Gleeson 2005;Vallee and Tsai 2006). Recently, purified LIS1 has been shown to enhance the microtubule-stimulated ATPase activity of the dynein motor (Mesngon et al 2006). Cytoplasmic dynein heavy chain, which contains the ATPase and the microtubule-binding domains, is responsible for motility.…”
mentioning
confidence: 99%
“…In the hyphae, endosomes are moved to the hyphal apex by kinesin-3, where they are loaded onto dynein motors for reverse movement 76 . Uploading of endosomes onto dynein is dependent on dynactin and LIS1 (a dynein activator that is defective in patients with the brain disorder lissencephaly 77,78 ), which both accumulate at microtubule plus ends. The functional significance of bidirectional endosome movement needs to be clarified, but it might be either to keep these organelles dispersed in the cytoplasm 79 , to enhance encounters between different compartments for subsequent fusion 68 , or to support fission 61 .…”
Section: Box 2 | Modes Of Motor-cargo Associationmentioning
confidence: 99%
“…LIS1 directly binds to multiple sites within dynein heavy chain, including the stem domain and the AAA1 domain (ATPase associated with diverse cellular activities), which is the site for ATP hydrolysis (9). Purified recombinant LIS1 is shown to increase the microtubule-stimulated ATPase activity of the dynein motor in vitro (10). Recent studies indicate that LIS1 is able to suppress the motility of dynein on microtubules (11).…”
mentioning
confidence: 99%